Preparation and Characterization of Amide-Containing Polyimide Films with Enhanced Tribopositivity for Triboelectric Nanogenerators to Harvest Energy at Elevated Temperatures - Zhen Pan; Shunqi Yuan; Yan Zhang; Xi Ren; Zhibin He; Zhenzhong Wang; Shujun Han; Yuexin Qi; Haifeng Yu; Jingang Liu (Nanoenergy Advances)
As triboelectric nanogenerator (TENG) technology continue to evolve, its application in harsh environments has increasingly captivated the interest of researchers. However, the current research on heat-resistant triboelectric materials remains predominantly focused on the development of tribo-negative materials, with scant attention given to their equally crucial tribo-positive counterparts. In this study, the tribo-positive polyimide (PI) material with enhanced tribo-positivity is developed by integrating amide groups with electron-donating effects into the molecular chain. Furthermore, the TENG devices based on this series of tribo-positive PI materials have demonstrated an open-circuit voltage (VOC) of 242 V, a short-circuit current (ISC) of 8.13 μA, and a transferred charge (QSC) of 117 nC. Notably, these devices also demonstrate the capability to efficiently generate electricity even under elevated temperature conditions. This work not only proposes a potential molecular design strategy for developing high-performance tribo-positive PI materials applicable in TENGs, but also markedly propels the advancement of robust energy-harvesting devices engineered for operation at elevated temperatures.